Identification of an antibody‐based immunoassay for measuring direct target binding of RIPK1 inhibitors in cells and tissues. Issue 6 (6th December 2017) - Finger, Joshua N.; Brusq, Jean‐Marie; Campobasso, Nino; Cook, Michael N.; Deutsch, Jennifer; Haag, Heather; Harris, Philip A.; Jenkins, Earl L.; Joglekar, Devika; Lich, John D.; Maguire, Sean; Nagilla, Rakesh; et al.
Abstract: Therapies that suppress RIPK1 kinase activity are emerging as promising therapeutic agents for the treatment of multiple inflammatory disorders. The ability to directly measure drug binding of a RIPK1 inhibitor to its target is critical for providing insight into pharmacokinetics, pharmacodynamics, safety and clinical efficacy, especially for a first‐in‐class small‐molecule inhibitor where the mechanism has yet to be explored. Here, we report a novel method for measuring drug binding to RIPK1 protein in cells and tissues. This TEAR1 (T argetE ngagementA ssessment forR IPK1 ) assay is a pair of immunoassays developed on the principle of competition, whereby a first molecule (ie, drug) prevents the binding of a second molecule (ie, antibody) to the target protein. Using the TEAR1 assay, we have validated the direct binding of specific RIPK1 inhibitors in cells, blood and tissues following treatment with benzoxazepinone (BOAz) RIPK1 inhibitors. The TEAR1 assay is a valuable tool for facilitating the clinical development of the lead RIPK1 clinical candidate compound, GSK2982772, as a first‐in‐class RIPK1 inhibitor for the treatment of inflammatory disease.